Between the Lines: The Innovation of Embroidery and Lace Through Art and Design in the Azores. (4th May 2019) - Nolasco, Ana
Abstract: This article focuses on emerging trends in embroidery and lace on the archipelago of the Azores, the role that such handicrafts have played in the circumstances of women on the islands throughout the twentieth century, and the profound effect of globalization on the development of embroidery and lace production and consumption. I will argue that art, craft, and design in these contexts come together to produce an interdisciplinary reciprocal dialogue and constitute mature political gestures as part of a global counter-hegemonic movement. At the same time as salvaging the silenced voices of women, they transform gestures marginalized by the spirit of consumer society into an affirmation of a particular way of life, reaffirming female identity through action.